Cerebrovascular accident (stroke): risk indicators profile - Rafaella Pessoa Moreira; Thelma Leite de Araújo; Tahissa Frota Cavalcante; Nirla Gomes Guedes; Marcos Venícios de Oliveira Lopes; Alice Gabrielle de Sousa Costa; Daniel Bruno Resende Chaves (Rev Rene)
The knowledge about risk indicators can more effectively subsidize strategies formulation to people with stroke. The aim of the study was to identify the risk indicators in stroke survivors. This is a cross-sectional study, developed with 121 patients of rehabilitation units in Fortaleza. The data were collected from November 2007 to march 2008, through interviews. The average age of the patients (± 12,4) was 61,6 years. Most of them were male (52,9%). The patients presented an average of 1,4 (± 1,0) stroke episodes. Among the risk indicators that most of them presented was hypertension (85,1%), followed by sedentary lifestyle (58,7%) and dislipidemia (29,8%). It was concluded that hypertension was the most common risk indicator in the patients and that control measures could be implemented to reduce the risk of other stroke events.